Investment under Rational Inattention: Evidence from US Sectoral Data - Peter Zorn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
I document the effects of macroeconomic and sector-specific shocks on investment in disaggregate sectoral capital expenditure data. The response of sectoral investment to macroeconomics shocks is protracted and hump-shaped, just as in aggregate data. By contrast, the effects of sector-specific innovations are short-lived and monotonically decreasing. I build a model of investment with rational inattention to explain these facts. The model predicts protracted effects of aggregate shocks and short-lived effects of sector-specific shocks on sectoral investment.
Keywords: E22; E32; D83; 330